Abdominal contusion in a patient with an inguinal hernia: small intestine rupture - Camaño, Mario C; Amorín Cal, Raúl (Cirugía del Uruguay, 2020)
The paper analyses the possible role of a hernia as a determinating factor in an intestinal lesion in cases of abdomen contusions. One case is presented.